From Mazouco to Foz do Tua and Passadeiro: continuities and changes in hunter-gatherers and early farmers of the lower Douro river basin (Portugal) revealed through rock art - Sanches, Maria de Jesus (2021)
This paper focuses on the prehistoric rock art and the archaeological research on the lower Douro river basin (Portugal), between the Upper Palaeolithic and the beginning of the Neolithic. It will begin with a brief reference to the first discovery, in 1981, of a rock with Palaeolithic engravings - on the site of Mazouco - and to the unusual circumstance of the lack of continuity of the regional Palaeolithic archaeological, which might have prevented the surprising discovery of the valuable rock art complex of the Côa Valley. Next, we will discuss the chronological and cultural contextualization of the figurative, schematic and abstract art - especially of the devil claw engravings - which is assigned to a period between the end of the Late Glacial and the regional Ancient Neolithic. Implicit in our discussion is the assumption that during this chronological period (c. 13,000/12,000 - 6500/6000 cal BP; 11,000/10,000 - 5000/4500 cal BC), the hunter-gatherer communities, regardless of whether they have adopted agriculture and animal husbandry around 6500 BP (4500 BC),"did not know" beforehand what would happen next or how their economies and relationships with the landscape, animals and plants would change. In the text, we defend that the rock art of this period, and of this region - even if it shows graphic similarities, especially in the design of zoomorphs and anthropomorphs, with other regions of Iberia and Southwest Europe - has an idiosyncrasy, evident for instance in the schematism and abstractionism of the engravings of "devil claw & thin linear motifs" that should be taken into account. This idiosyncrasy must be understood within the tissue of the identitary relationships between different hunter-gatherer communities and among each other and the landscapes where they dwell.